Florida 4-H Tailgate: Smoking and Slow Cooking Meat - Chad Carr; Brian Estevez; Sonja Crawford; Jason Scheffler; George Baker; Ed Jennings; Mark Mauldin (EDIS)
The Florida 4-H Poultry BBQ program has existed for years, and the program for red meat cookery has been a huge success in Tennessee 4-H. With sponsorship for the winners at the state level, the Florida 4-H Tailgate Contest program will be a success in Florida as well. This program will strive to promote enjoyable outdoor cooking experiences, encourage the incorporation of animal protein in the diet in order to combat childhood obesity, improve youth nutritional knowledge and cooking skills, and impart knowledge about safe handling and proper degree of doneness to produce safe and delicious meat dishes. This 2-page fact sheet is the fourth publication in the Florida 4-H Tailgateseries, and it discusses smoking and slow cooking meat. Written by Chad Carr, Brian Estevez, Sonja Crawford, Jason Scheffler, George Baker, Ed Jennings, and Mark Mauldin, and published by the 4-H Youth Development Department, December 2016. http://edis.ifas.ufl.edu/4h375